Tuberculosis patients in the Dominican Republic face severe direct and indirect costs and need social protection Los pacientes con tuberculosis en la República Dominicana afrontan altos costos directos e indirectos, y necesitan protección social - Verena Mauch; Ricardo Melgen; Belkys Marcelino; Ivelisse Acosta; Eveline Klinkenberg; Pedro Suarez (Pan American Health Organization, 2013)
OBJECTIVE: To examine direct and indirect costs incurred by new, retreatment, and multidrug-resistant (MDR) tuberculosis (TB) patients in the Dominican Republic before and during diagnosis, and during treatment, to generate an evidence base and formulate recommendations. METHODS: The "Tool to Estimate Patients' Costs" was adapted to the local setting, translated into Spanish, and pretested. Patients attending 32 randomly selected health facilities in six chosen study areas on the study days were interviewed. Responses from patients 18-65 years old who had received treatment for at least one month and provided signed informed consent were collected, entered into a database, and analyzed. RESULTS: A total of 200 patients were interviewed. For most respondents, direct and indirect costs increased while income decreased. Total costs amounted to a median of US$ 908 for new patients, US$ 432 for retreatment patients, and US$ 3 557 for MDR-TB patients. The proportion of patients without a regular income increased from 1% to 54% because of falling ill with TB. Following its review of the study results the Ministry of Health has made efforts to allocate public funds for food supplements and to include in- and outpatient TB services in the national health insurance schemes. CONCLUSIONS: Free TB diagnosis and treatment are not enough to alleviate the financial constraints experienced by vulnerable groups as a result of the illness. Health insurance covering TB in- and outpatient costs is critical to prevent TB-related financial hardship. OBJETIVO: Examinar los costos directos e indirectos afrontados por los pacientes con tuberculosis en la República Dominicana, ya sea por un tratamiento nuevo, por retratamiento, o por una tuberculosis multirresistente (MR), antes y a lo largo del proceso diagnóstico y durante el tratamiento, con objeto de generar una base de datos probatorios y formular recomendaciones. MÉTODOS: El "Instrumento de cálculo de los costos afrontados por los pacientes" ("Tool to Estimate Patients' Costs") se ...